2014
DOI: 10.1111/jcom.12127
|View full text |Cite
|
Sign up to set email alerts
|

Hallin and Mancini Revisited: Four Empirical Types of Western Media Systems

Abstract: The analysis of media systems has become a cornerstone in the field of comparative communication research. Ten years after its publication, we revisit the landmark study in the field, Hallin and Mancini's "Comparing Media Systems", and operationalize its framework for standardized measurement. The study at hand is, to the best of our knowledge, the first to comprehensively validate the original dimensions and models using aggregated data from the same sample of Western countries. Three out of four dimensions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
367
0
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(393 citation statements)
references
References 17 publications
9
367
0
17
Order By: Relevance
“…Współcześnie badacze posiłkują się głównie koncepcją trzech modeli mediów i polityki w ujęciu porównawczym sformułowaną przez D. Hallina i P. Manciniego w pracy opublikowanej w 2004 r. Co prawda, nie wszyscy zgadzają się z przypisaniem do poszczególnych modeli (liberalnego, demokratycznego korporacjonizmu i spolaryzowanego pluralizmu) określonych państw (Brüggemann, Engesser, Büchel, Humprecht, Castro, 2014), niemniej jest to praca stanowiąca punkt odniesienia dla szeregu nowych badań nad relacją pomiędzy systemem politycznym a systemem medialnym (DobekOstrowska, 2010;2012), również tych prowadzonych ponownie pod kierunkiem D. Hallina i P. Manciniego (2012).…”
Section: Poznańunclassified
“…Współcześnie badacze posiłkują się głównie koncepcją trzech modeli mediów i polityki w ujęciu porównawczym sformułowaną przez D. Hallina i P. Manciniego w pracy opublikowanej w 2004 r. Co prawda, nie wszyscy zgadzają się z przypisaniem do poszczególnych modeli (liberalnego, demokratycznego korporacjonizmu i spolaryzowanego pluralizmu) określonych państw (Brüggemann, Engesser, Büchel, Humprecht, Castro, 2014), niemniej jest to praca stanowiąca punkt odniesienia dla szeregu nowych badań nad relacją pomiędzy systemem politycznym a systemem medialnym (DobekOstrowska, 2010;2012), również tych prowadzonych ponownie pod kierunkiem D. Hallina i P. Manciniego (2012).…”
Section: Poznańunclassified
“…When examining national differences another topic arises, which deserves clarification. Research demonstrated the existence of different types of national media systems in Europe and beyond (Brüggemann et al 2014;Büchel et al 2016;Hallin and Mancini 2017). We cannot, however, enter the debate on the construction and validation of these types here, as the empirical data are too specific regarding its focus on public intellectuals and too restrained to characterize the media landscape of entire countries.…”
Section: Research Questions and Research Designmentioning
confidence: 99%
“…In comparison, Norway, a nation of approximately 5 million people, is relatively homogenous and insular but provides a stronger social safety net and is more socially integrated. Beyond basic cultural and geographic differences, there are also clear political and media divergences between the two countries (Brüggemann et al 2014;Aalberg & Curran 2013).…”
Section: National Context and News Media Orientationmentioning
confidence: 99%
“…Will these effects be consistent across the globe? We argue that the effects of increased media choice around the world will likely differ as a result of locale-specific idiosyncrasies (Brüggemann et al 2014;Bijker, Hughes, & Pinch 2012).…”
Section: National Context and News Media Orientationmentioning
confidence: 99%